Women's Leadership Style in the Pelikan Dasawisma in Sidoarjo - Fira Magfira Ovalia (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
The purpose of this study is to identify the leadership communication style of women at Dasawisma Pelikan. In Indonesia, women are still generally thought to be inferior and unable to hold senior management roles in organizations, gender gaps are still frequently observed. People's perspectives on gender equality have been impacted by the advancement of communication technologies. In Indonesia, gender equality has increased recently, and women are now frequently in positions of leadership. A lady who has led Dasawisma for seven years is in charge of the organization. This study intends to ascertain the communication style used by female leaders at Dasawisma Pelikan in light of the context mentioned above. Data were collected through interviews and observations utilizing purposive sampling as part of a qualitative research project employing an ethnographic communication methodology. This study found that being a single parent is similar to being a leader in that it fosters empathy and sympathy for others, which motivates women to take on leadership roles.